Pressing Play: Digital Game Techniques and Interactive Art. (November 2014) - Pierce-Grove, Ri
Interactive art often requires viewers to interact playfully with it in order to experience it fully, so it is reasonable to ask how game techniques and the theory of play can aid in its creation and interpretation. This article introduces the idea of "magical objects, " familiar things given unexpected and fantastical properties by concealed technology, and analyzes certain interactive art installations in this light. As a case study, it uses Fragments, an installation of interactive silk tapestries that whispered verse to the viewer when passed or touched. Fragments drew on techniques from digital games and play to reimagine the materiality of the book and engage contemporary urban experience. In doing so, it offered a model for the incorporation of playful thinking into the design of both installation art and educational displays.